Acute pancreatitis- a clinical update - Ahad, Md Abdul (Bangladesh Medical Journal Khulna, 2018)
Acute pancreatitis is an acute inflammatory process of the pancreas that can range from mild interstitial pancreatitis to severe pancreatitis with pancreatic necrosis with variable involvement of regional tissues and remote organ systems. The incidence of pancreatitis varies in different countries and depends on causes e.g, gallstones, alcohol, metabolic factors and viral infections. Gall stones continue to be the leading cause of acute pancreatitis in most series. Alcohol, hypertriglyceridemia and drugs are also a common cause of acute pancreatitis. Gall stone pancreatitis is more common in women than in men. Alcohol is also a common cause of acute pancreatitis. Alcoholic pancreatitis is more common in men, and usually occurs in individuals with long standing alcohol abuse. The increased frequency of acute pancreatitis may be due to the rising incidence of obesity, a risk factor for the development of gallstones and by extension, gallstone pancreatitis. Acute pancreatitis occurs when there is abnormal activation of digestive enzymes within the pancreas. This occurs through inappropriate activation of inactive enzyme precursors called zymogens or proenzymes inside the pancreas, most notably trypsinogen. Acute pancreatitis is typically rapid in onset and most commonly encountered in its mild form. While mild cases are often successfully treated with conservative measures, such as fasting and aggressive intravenous fluid rehydration, severe cases may require admission to the intensive care unit or even surgery to deal with complications of the disease process. Acute pancreatitis may be accompanied by life threatening complications as well as significant morbidity and mortality despite treatment. Bang Med J (Khulna) 2017; 50 : 35-40